2006
DOI: 10.1111/j.1440-1797.2006.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein restriction as a treatment for slowing chronic kidney disease progression: The case against (Review Article)

Abstract: Low-protein diets ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 55 publications
(96 reference statements)
0
27
0
Order By: Relevance
“…These studies generally provided KA/EAA supplementation of w0.28 g/kg/d with protein at a level of w0.30 g/kg/d. 9,42,66,71 The MDRD Study maintained good nutrition with similar KA/EAA supplementation. 67,68 Currently, KA/EAA levels of w100 to 126 mg/kg/d often are prescribed 61,69 ; this reduces the cost of treatment and should facilitate patient acceptance.…”
Section: Protein-energy Statusmentioning
confidence: 98%
“…These studies generally provided KA/EAA supplementation of w0.28 g/kg/d with protein at a level of w0.30 g/kg/d. 9,42,66,71 The MDRD Study maintained good nutrition with similar KA/EAA supplementation. 67,68 Currently, KA/EAA levels of w100 to 126 mg/kg/d often are prescribed 61,69 ; this reduces the cost of treatment and should facilitate patient acceptance.…”
Section: Protein-energy Statusmentioning
confidence: 98%
“…They had stable renal function for at least 12 weeks before enrollment (defined as a reduction in eGFR,4 ml/min per year 24 , proteinuria ,1 g/g urinary creatinine, good nutritional status as indicated by an SGA score A/B, and serum albumin $3.5 g/dl). Only the patients who declared a potentially good compliance with an LPD and agreed to follow the monitoring schedule were considered.…”
Section: Subjectsmentioning
confidence: 99%
“…21 Notably, patients' adherence to LPD was also a problem. 21 Because the efficacy of protein-restricted regimens seemed uncertain, 20 their feasibility was repeatedly questioned; because the adherence and compliance of patients to the diet were reported as poor and the risk of malnutrition was frequently invoked, [22][23][24][25] the use of KD and VLPDs was not extended.…”
mentioning
confidence: 99%
“…The authors found that patients treated with a VLPD experienced a signiicant 36% reduction in serum IS levels compared with those treated with a LPD (7.12 ± 3.89 μM during VLPD vs. 11.1 ± 6.6 μM during LPD, p < 0.0001). Although a meta-analysis has identiied reduction in the occurrence of renal death with a lowprotein intake in CKD patients, the overall value of these diets remains a subject of debate, given that the risks of malnutrition may present a greater danger [30][31][32]. Furthermore, poor compliance is also likely to be an issue, as participants often did not meet dietary targets even with the intensive support provided within a trial seting.…”
Section: Reduced Gut Synthesismentioning
confidence: 99%